Algorithm-based analysis of lymph node dissection strategies and survival outcomes in primary oral squamous cell carcinoma - Vollmer, Andreas; Saravi, Babak; Kübler, Alexander; Müller-Richter, Urs; Winter, Anna; Nagler, Simon; Hörner, Marius; Gubik, Sebastian; Hartmann, Stefan (Frontiers in Oncology, 2025)
IntroductionRecent advancements in treatment approaches for oral squamous cell carcinomas (OSCCs) necessitate a reevaluation of neck dissection techniques and their impact on patient outcomes and morbidity.MethodsThis retrospective study of 250 OSCC patients recruited between 2017–2022 examined the association between neck dissection techniques and survival metrics. Our cohort, drawn from a primary OSCC surgery population at our clinic, provided a rich dataset encompassing demographics, clinical parameters, and detailed surgical records. Two neck dissection techniques were analyzed: the Supraomohyoid Selective Neck Dissection (SND), which targets lymph nodes at Levels I–III, and Other Dissections (OD), which involve a more extensive extraction including Levels IV and V. Kaplan-Meier survival curves and Cox proportional hazards models assessed the influence of lymph node dissection on postoperative outcomes.ResultsFindings indicated that each additional lymph node removed was associated with a 0.289-day increase in hospitalization (p = 0.002), yet no significant link was found between dissection techniques or total lymph node extraction count and survival metrics. Levels I to III emerged as critical areas with the highest likelihood of yielding tumor-positive lymph nodes, emphasizing the significance of these levels.DiscussionThe study suggests that more extensive dissection does not necessarily confer survival benefits, highlighting the importance of strategic surgical focus and the potential for tailored interventions that prioritize disease-specific lymph node levels to optimize patient recovery and prognosis.